Paper of RILEM TC 282-CCL: mineralogical characterization methods for clay resources intended for use as supplementary cementitious material - Snellings, Ruben; Almenares Reyes, Roger; Hanein, Theodore; Irassar, Edgardo F.; Kanavaris, Fragkoulis; Maier, Matthias; Marsh, Alastair T.; Valentini, Luca; Zunino, Franco; Alujas Diaz, Adrian (Materials and structures, 2022)
To respond to the rapid introduction and development of calcined clays as supplementary cementitious material (SCM), the toolbox of characterization methods for cementitious materials requires extension to raw clay characterization. Borrowing concepts and methods developed in the field of clay mineralogy, this paper outlines the merits and limits of widely accessible characterization techniques for raw clays intended for use as SCM, when calcined. The paper focuses mainly on the identification and quantification of the raw clay mineral components, as these characteristics have important implications for further material processing and performance. General notes are provided on clay sampling and pre-treatment as well as bulk chemical analysis. The main techniques considered are X-ray diffraction, thermal analysis and infrared spectroscopy. Their application on raw clays is introduced, highlighting clay-specific aspects of sample preparation, data acquisition, and processing. Guidelines and interpretation tables are provided to aid in the analysis of the acquired data, while limitations and potential interferences are identified. Options for remote prospection by infrared spectroscopy are included as well. To illustrate the type of information to be gained and the complementarity of the techniques, two representative raw clays are fully characterised. This paper aims to highlight that mineralogical characterization is a feasible and often necessary step in the study and assessment of raw clays that can deliver a wealth of informative data if carried out appropriately.